PENGGUNAAN TEKNIK REVERSE LENS DALAM PEMOTRETAN FOTOGRAFI MAKRO - Sulistiyo Wibowo (Jurnal Ilmiah Publipreneur, 2016)
Something that we don't normally see whether because of something we rarely find or indeed we often find, but we pay less attention in depth because it might be of a size that is too small so it doesn't 'steal' our attention. Large and clear details are common when we observe things, especially objects around us. Butwhat if we want something that is more and less exposed because of its small size. Many simple things are used such as by bringing our eyes closer to the object to use tools such as a magnifying glass or even a microscope if it is needed. Raising a small subject is actually not unusual in the world of photography. The term photography in photography is called macro photography, which is shooting with small objects or subjects with the help of lenses or special tools so that the small-looking subject will appear large and theÂ details of the subject will be unclear. For some people photography equipment might be considered expensive compared to mobile phones that have been equipped with cameras, especially when discussing equipment related to macro photography. Basically, macro shooting is the same as ordinary shooting, but the lens andsupporting equipment are slightly different. Especially lenses that do require a macro lens that has a tight focal point and are relatively expensive in price. But now there are many different converters for macro photography that are mounted on a normal lens, although the quality will indeed be different when we use an actual macro lens. In this study the author will put more emphasis on macro photography using the Reverse Lens technique. Reverse Lens is a technique by reversing the normal lens position and attaching it to the camera body mounting. Because reversing the lens mount requires an adapter so that it can be installed in the camera body so the shooting process will be more comfortable. Hopefully this research can provide useful results and interesting photography.